DESIMINASI PENGUATAN KEPENGAWASAN KEPALA SEKOLAH SUBRAYON SMPN 1 DAMPIT DAN SMPN 1 KALIPARE KABUPATEN MALANG JAWA TIMUR - Susatri, Hidayah; Kimberly Ann, Amelia; Isrofin, Anis; Payong, Yohanes; da Silva, João; Supriyanto, Achmad (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2024)
Strengthening supervision in educational institutions at various levels, one at the junior secondary school level, is very important. Principals, as supervisors and vice-principals for curriculum, are the key people who will assist teachers in proper supervision. Recognizing the importance of the above, it is necessary to provide supervisory guidance from the community in line with the direction of strengthening school-based supervision. This Community Service activity (PKM), held on May 4, 2024, will strengthen supervision in State Junior High School (SMPN) educational institutions. The method used is to provide enlightenment through training to Principals, Vice Principals for Curriculum, and Teachers using lectures, discussions, and question-and-answer methods. The results of this PKM activity show that the principals and teachers can formulate a school-based supervision model from various supervision models that can be applied in each school, both in the SMPN 1 Dampit Sub Rayon and SMPN 1 Kalipare Sub Rayon. In this program, they can formulate various supervision models such as situational leadership, humanistic, cura personalis, learning supervision, and school-based supervision effectiveness models that can be implemented in these schools.